Genome analysis of three Pneumocystis species reveals adaptation mechanisms to life exclusively in mammalian hosts - Liang Ma (Nature Portfolio, 2016)
Pneumocystis jirovecii is a fungus that can cause life-threatening pneumonia in immunocompromised patients. Here, the authors sequence the genomes of P. jirovecii and two other Pneumocystisspecies, and show the unexpected absence of chitin (a near universal fungal cell wall component).